2023
DOI: 10.2147/jir.s409871
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/Lymphocyte Ratio (NLR) and Lymphocyte/Monocyte Ratio (LMR) – Risk of Death Inflammatory Biomarkers in Patients with COVID-19

Abstract: Aim The aim of our retrospective study was search for new prognostic parameters, which can help quickly and cheaply identify patients with risk for severe course of SARS-CoV-2 infection. Materials and Methods The following peripheral blood combination biomarkers were calculated: NLR (neutrophil/lymphocytes ratio), LMR (lymphocyte/monocyte ratio), PLR (platelet/lymphocyte ratio), dNLR (neutrophils/(white blood cells − neutrophils)), NLPR (neutrophil/(lymphocyte × platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Our previous multicentre study in Saudi Arabia demonstrated the prognostic value of the NLR in detecting severe COVID-19 cases, i.e., admitted to the ICU, compared to both non-severe cases and non-COVID-19 patients [9]. Such a finding was later confirmed and was found to be applicable to other cohorts locally [15,16] and internationally [17][18][19]. More recently, the works of Regolo et al demonstrated the value of the NLR as an independent predictor of mortality in separate studies including over 1000 patients with COVID-19 [20,21].…”
Section: Discussionmentioning
confidence: 72%
“…Our previous multicentre study in Saudi Arabia demonstrated the prognostic value of the NLR in detecting severe COVID-19 cases, i.e., admitted to the ICU, compared to both non-severe cases and non-COVID-19 patients [9]. Such a finding was later confirmed and was found to be applicable to other cohorts locally [15,16] and internationally [17][18][19]. More recently, the works of Regolo et al demonstrated the value of the NLR as an independent predictor of mortality in separate studies including over 1000 patients with COVID-19 [20,21].…”
Section: Discussionmentioning
confidence: 72%
“… 15 , 24 Additionally, dNLR is a variable in risk-scoring models which associate with critical illness in COVID-19 patients. 25 Several studies have recognized its independent significance in affecting mortality. 16 , 26 Similarly, our study confirmed that dNLR >5.0 was associated with death in patients with severe omicron infection.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to the infection is complex and highly individualized, which undoubtedly affects the severity of disease symptoms and complications after the infection. 1 Research has shown that severe COVID-19 is not directly caused by the SARS-CoV-2, but by the cytokine storm which increases the production of reactive oxygen species (ROS) that induce oxidative stress. 2 An infection caused by the SARS-CoV-2 leads to the activation of neutrophils and mononuclear phagocytic cells which are largely responsible for the massive release of ROS in lung tissues.…”
Section: Introductionmentioning
confidence: 99%